(untitled) - Ostrander, Gary K. (Boca Raton, 2005)
Following up on his popular Techniques in Aquatic Toxicology with a second volume, now nine years later, Dr. Ostrander has once again called on the top aquatic toxicologists from across the world to present 39 chapters of unique collection and testing procedures. Updating five techniques from the first volume, the authors have gone on to add over two dozen new techniques. Every chapter covers a specific procedure that can easily be reproduced by any competent technician with basic knowledge. Each of the chapter authors provides and interprets typical and anomalous results, false positives, and artifacts. Data is provided either from recently published experiments or from work being published for the first time.
Keywords: Water quality bioassay,Water; Technique,Pollution,Toxicology,Measurement